Measurement of the crystallization and phase transition of niobium dioxide thin-films using a tube furnace optical transmission system - Zachary R. Robinson; Karsten Beckmann; James Michels; Vincent Daviero; Elizabeth A. Street; Fiona Lorenzen; Matthew C. Sullivan; Nathaniel Cady; Alexander C. Kozen; Jeffrey M. Woodward; Marc Currie (AIP Advances)
Niobium dioxide has a volatile memristive phase change that occurs ∼800 °C that makes it an ideal candidate for future neuromorphic electronics. A straightforward optical system has been developed on a horizontal tube furnace for in situ spectral measurements as an as-grown Nb2O5 film is annealed and ultimately crystallizes as NbO2. The system measures the changing spectral transmissivity of Nb2O5 as it undergoes both reduction and crystallization processes. We were also able to measure the transition from metallic-to-non-metallic NbO2 during the cooldown phase, which is shown to occur about 100 °C lower on a sapphire substrate than fused silica. After annealing, the material properties of the Nb2O5 and NbO2 were assessed via x-ray photoelectron spectroscopy, x-ray diffraction, and 4-point resistivity, confirming that we have made crystalline NbO2.